The Terminology of the Theory of Population - Mixter, C. W. (Quarterly Journal of Economics, 1905)
The Terminology of the Theory of Population Get access C. W. Mixter C. W. Mixter The University of Vermont Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 19, Issue 2, February 1905, Pages 314–315, https://doi.org/10.2307/1882868 Published: 01 February 1905